(untitled) (Studia austriaca, 2022)
This article examines how David Schalko’s series Braunschlag (2012) presents a community that is threatened by disintegrative forces and dysfunctional communications. The series is read as a political allegory on postmodernist struggles in Austrian culture – as a laboratory for western European societies in general – between globalisation and provincialism. As this is linked to aspects of popular culture in the series, the article includes theoretical thoughts about popular cultural “common grounds” with their inclusive and exclusive function, as analysed by M. Bauer, U. Eco and M. Tomasello.